A rare case of hypertrophic olivary degeneration in a patient with pontine hemorrhage - Mamytova, Elmira; Biialieva, Gulmira; Akulich, Evgeniya; Abaeva, Tamara; Monolov, Nurbek; Satybaldiev, Masalbek; Chekirbaeva, Nursulu; Batyrov, Maksatbek (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Hypertrophic olivary degeneration (HOD) is an extremely rare disease that affects the inferior olivary nucleus (ION) in the medulla oblongata and is also referred to as hypertrophic degeneration of the inferior olives. This type of degeneration is characterized by trans-synaptic degeneration resulting from the blocking of afferent impulses in the ION, which is distinct from HOD. In this report, we present a clinical case of bilateral HOD that was identified and confirmed by neuroimaging two months after pontine hemorrhage. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 52-year-old male was admitted to a university hospital because of gait imbalance, difficulty in swallowing and speaking, psychomotor agitation, visual hallucinations, and full vertical and horizontal gaze paralysis. He had a history of hypertension, hyperlipidemia, and obesity. The patient received symptomatic supportive treatment, without surgery. Ten weeks after the vascular incident, neurological examination revealed six cases of right cranial nerve palsy, vertical pendular nystagmus, dysarthria, decreased throat reflexes, and lingual and pharyngeal paresthesia. Repeated magnetic resonance imaging revealed bilateral hyperintense foci of 15×6 mm in the medulla oblongata, as detected by T2-weighted and fluid-attenuated inversion recovery. Two months of treatment with clonazepam, carbamazepine, and vestibular exercise resulted in no positive changes. Rehabilitation and psychotherapy were then continued. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Contrast MRI is required to confirm HOD, whereas non-contrast magnetic resonance imaging is the only method used for imaging and is not always reliable because it can cause neoplasia, infarction, demyelinating disorders, infections, and other similar problems.